Aerial ramet dynamics and general clonal growth patterns of scirpus grossus in grown at different water depths and fertilizer regimes in paddy soils - Mohammad Moneruzzaman, Khandaker; Ali, Majrashi; Baki, Bakar (2015)
Scirpus grossus L. is a principal rhizomatous weed in the rice fields, drainage and irrigation canals, river banks, abandoned rice fields and wasteland in Malaysia. This study provides evidences that plants of S. grossus have a remarkable ability to alter their development in response water depth regimes. This phenotypic plasticity allows them to continually adapt to their local environment, a necessity for plants as sessile organisms. The results of this current study showed that devoid of fertilizer application (F0) and not inundated, S. grossus plants with mean monthly population counts up to 16 weeks, taken at 4-weekly intervals were as follows: 61.33, 67.33, 75.33 and 117.00 plants m–2. With fertilizer applications, the parallel counts for F2 (64.67, 71.00, 80.33 and 34.33 plants m–2), F3 (65.33, 72.67, 68.33 and 32.00 plants m–2), F4 (71.67, 72.00, 71.67, 6.33 plants m–2), F5 (79.33, 74.67, 52.00 and 0.00 plants m–2), denoting increased mortality of ramets with increased fertilizer applications. Ramet mortality of S. grossus increased with the greater depths of the water level and with increasing NPK concentrations. It was also observed that population number of ramets decreased with increased depths of inundation, irrespective of fertilizer regimes. In relation to plant height, recorded results showed that plant height was highest in the 10 cm water depth treatment followed by 20, 5 and 0 cm water depth treatments, respectively. It can be concluded that depth of inundation and fertilizer regimes have significant effects on aerial growth and ramets mortality of Scirpus grossus.